Education Financing Management in Integrated Islamic Schools - Sinta Ningsih; Ai Rohaniah (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine how the management of education financing of Integrated Islamic Schools. The research method used is a literature review. Based on the results of data analysis, it is known that the funding of Integrated Islamic School education refers to the National Education Standard (SNP) contained in Government Regulation No. 19 of 2005 Chapter IX Article 62 concerning Financing Standards and related Ministerial Regulations (Regulation No. 69 of 2009). The Foundation as the manager of an integrated Islamic educational institution, carries out management as determined by the Integrated Islamic School Network as stated in the Integrated Islamic School Quality Standards. The Foundation has limitations in financing learning and extracurricular activities and procuring infrastructure facilities. There are several types of activities in which schools are given the authority to manage finances or sources of income.